2009
DOI: 10.1186/1471-2474-10-135
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life after vertebral or hip fracture: a seven-year follow-up study

Abstract: Background: The negative impact of vertebral and hip low-energy fractures on health-related quality-of-life (HRQOL) has been demonstrated previously, but few prospective long-term follow-up studies have been conducted. This study aims to (i) investigate the changes and long-term impact of vertebral or hip fracture and between fracture groups on HRQOL in postmenopausal women prospectively between two and seven years after the inclusion fracture, (ii) compare HRQOL results between fracture and reference groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
5
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 51 publications
4
63
5
3
Order By: Relevance
“…However, the variables in the statistical models explained between only 15 and 21 % of the variability within HRQoL scores in those with and without fracture, suggesting that other factors that are associated with BMD could be directly impacting on HRQoL in these patients. For example, it has been shown that levels of physical activity [35,36], grip strength [31] and sarcopenia [37] have been associated with HRQoL scores in postmenopausal women. Additionally, physical function domain scores on the SF36 have been associated with objectively measured physical function in men [38] and can be used as a valid measure of disability [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, the variables in the statistical models explained between only 15 and 21 % of the variability within HRQoL scores in those with and without fracture, suggesting that other factors that are associated with BMD could be directly impacting on HRQoL in these patients. For example, it has been shown that levels of physical activity [35,36], grip strength [31] and sarcopenia [37] have been associated with HRQoL scores in postmenopausal women. Additionally, physical function domain scores on the SF36 have been associated with objectively measured physical function in men [38] and can be used as a valid measure of disability [39].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is defined as a skeletal disorder characterized by compromised bone strength predisposing an individual to an increased risk of fracture (3). Osteoporotic fractures considerably reduce health related quality of life and are associated with an increased mortality later in life (4,5). The assessment of osteoporosis associated fracture risk has traditionally relied on the assessment of bone mineral density (BMD) at the spine and hip by using dual-energy X-ray absorptiometry (DXA) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Studier har vist at det å leve med osteoporoserelatert vertebralfraktur reduserer eldre kvinners helserelaterte livskvalitet og at den kan vaere redusert flere år etter deres første fraktur (6,9,10).…”
Section: Introduksjonunclassified